1991
DOI: 10.1039/c39910000570
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid complexed heteroatom carbanions; synthesis of some α-pyridyl alcohols

Abstract: Metallation of BF3-pyridine complex with lithium tetramethylpiperidide (LTMP) in ether at -78 "C, followed by reaction with carbonyl compounds, affords a-pyridyl alcohols in good yields. a-Pyridyl alcohols, which are intermediates of some pharmacological interest ,132 are often synthesised from halogen derivatives or N-oxides of pyridine because direct metallation of this heterocycle is deemed impractical.3-5 It was, therefore, of interest to see if Lewis acid complexation can be used for this purpose (Scheme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 9 publications
0
25
0
2
Order By: Relevance
“…Kessar et al reported the lithiation of pyridine aided by BF 3 complexation with lithium tetramethyl piperidine (LTMP). [15] However, it is for the first time that selective mono-and dilithiation of 3,5-lutidine ring has been achieved by using BF 3 -complexed 3,5-lutidine with lithium diisopropylamide (LDA) or lithium tetramethyl piperidine (LTMP). Single-crystal X-ray studies of bis(3,5-dimethyl-2-pyridyl) diselenide (5), having a rare CeSeeSeeC torsion angle of 180 (4), and 2,6-bis(selenomethyl)-3,5-lutidine (7) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Kessar et al reported the lithiation of pyridine aided by BF 3 complexation with lithium tetramethyl piperidine (LTMP). [15] However, it is for the first time that selective mono-and dilithiation of 3,5-lutidine ring has been achieved by using BF 3 -complexed 3,5-lutidine with lithium diisopropylamide (LDA) or lithium tetramethyl piperidine (LTMP). Single-crystal X-ray studies of bis(3,5-dimethyl-2-pyridyl) diselenide (5), having a rare CeSeeSeeC torsion angle of 180 (4), and 2,6-bis(selenomethyl)-3,5-lutidine (7) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…31 Initially, the synthesis of diketone 22 directly from Weinreb amide 19 and 4-DMAP 20 was attempted using Fort's direct 5 deprotonation protocol, 32 however this was unsuccessful. Kessar 33 used N-trifluoroboration of pyridine to acidify the 2-position of the ring, and the resulting pyridinium ylid was used for C-C bond-formation. The same BF 3 adduct has also been utilized by Sammakia 34 of the configurational isomers are very high relative to 26, (density functional calculations using the B3LYP 6-31G* functional in a DMF continuum show that changing one of the inter-ring alkenes from E to Z affords the next most favourable isomer, but that is 23 kcal/mole higher in energy than 26) and 5 accordingly, populations of minor isomers arising in this way are unlikely as the cause of the broad signals in the NMR spectrum.…”
mentioning
confidence: 99%
“…(4-Methylpyridin-2-yl)(phenyl)methanone (2e): [12] Column chromatography (hexanes/EtOAc, 90:10) yielded 2e (614 mg, 78%) as a yellow oil. (4-Methylpyridin-2-yl)-3-phenylmethanol (2f): [6] Column chromatography (hexanes/EtOAc, 70:30 ) yielded 2f (476 mg, 60%) as a beige solid. 1 Methylpyridin-2-yl)butan-2-ol (2g): Column chromatography (hexanes/EtOAc, 50:50) yielded 2g (449 mg, 68%) as an orange oil.…”
Section: Materials and Solventsmentioning
confidence: 99%
“…This Scheme 1 was accomplished by treatment of 1 with BF 3 ·OEt 2 and subsequent lithiation with an excess of LTMP, and is known as Kessar's reaction. [6] Although efficient, this process implies the regeneration of neutral substituted pyridine from the BF 3 Ϫpyridinium species. Our approach is to incorporate the pyridine nitrogen atom into nBuLi-containing lithium aggregates, [7] the enhancement of proton acidities and proximity effects being expected to promote selective C-2 lithiation ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%